David Copperfield - Dickens, Charles, 1812-1870.; Attenborough, Richard; Clark, Cyril; Evans, Edith; Digiview Productions ([Dunellen, N.J.] : Digiview Productions, 2004)
Told in flashback style with a combination of good advise and abusive acts against him, David's journey through life is followed, beginning as a young orphan in Victorian England to an adult who finds resolution to his problems.
Based on the novel of the same title by Charles Dickens.
Richard Attenborough, Cyril Clark, Edith Evans.
DVD.
Keywords: Feature films